Regatas y la afluencia de turistas en el Rio Vinces en el cantón Vinces - Fuentes Herrera, Marlen Lillybeth (2019)
This research has been carried out in order to know about the influx of tourists in the season of Regatas in the Vinces River of the city of Vinces and the contribution that it has provided to local, provincial and national development to raise awareness about the problematic that appears in this panorama regarding the tourist subject, since this activity generates quite considerable income and nevertheless it is not used in a good way. For this research has been used various types, methods and techniques of research, which helped to have a clear idea about the tourist resources that counts the canton Vinces, for it has been used bibliographic research, the same that allows to verify In a more specific way with previous research, it should be noted that the inductive-deductive method was also used, which allowed us to pay closer attention to the object of study. With the results obtained in the research carried out in this case study, it was possible to analyze more closely the object of study and reach the conclusion that it is necessary to carry out a tourism planning together with the Municipality in order to give greater emphasis and Another approach to this festival that takes place every year, making this tourism planning, is to make better use of resources, improving the quality of life of each of the citizens of Vince.